Efektivitas Model Think Talk Write (TTW) terhadap Kemampuan Menulis Teks Anekdot Siswa Madrasah Aliyah - Ayu Siti Aisyah; Tri Astuti; Indah Puspita Sari; Agung Nugroho (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effectiveness of the Think Talk Write (TTW) model on the ability to write anecdotal texts for class X MA Negeri 1 (Model) Lubuklinggau students. The research method used was quasi-experimental. Test data analysis techniques with steps to determine the average value and standard deviation, normality test, t test and non-test data techniques (Questionnaire). The results showed that the results of hypothesis testing and data analysis obtained tcount = 26,325 and Sig (2-tailed) that is 0.000.0 <0.05. Meanwhile, the non-test data (questionnaire) obtained from the recapitulation of the positive response data from students showed that the answers strongly agreed and agreed with 54.8%, in the good category. In conclusion, the use of the Think Talk Write (TTW) model is effective on the ability to write anecdotal texts for class X MA Negeri 1 (Model) Lubuklinggau students. Keywords: Effectiveness of Think Talk Write (TTW) Model, Ability to Write Anecdo Text